A partial-order-based approach for assessing multiple risks. Issue 7 (14th September 2017) - Carlsen, Lars; Bruggemann, Rainer
ABSTRACT: Risk assessment of chemicals consists of eight steps: 'hazard identification, effects assessment, exposure assessment, risk characterization, risk classification, risk–benefit analysis, risk reduction, and monitoring'. The present study deals with the following steps: exposure assessment, effects assessment, risk characterization, and risk reduction, and discusses to what extent a partial order framework can be helpful in the case of presence of simultaneous multiple risks. Applying simple tools out of the theory of partial order, it is concluded that it could be worth to deeper analyze the possibilities partial order concepts offer. As an example, air pollution in Yokohama and the related risks to the human health are described taking simultaneously three sites in consideration including seven typical urban air pollutants, i.e. benzene, toluene, ethylbenzene, o-, m-, p-xylene, as well as 1, 2, 4-trimethyl benzene, naphthalene, and methyl ethyl ketone. The overall risk is assessed leading to the conclusion that in the present case toluene appears as the most hazardous compound. It is further shown how risk reduction could be simulated, before an advice for management is to be articulated. It turns out that under the seven exemplary volatile chemicals, a management with respect to toluene could be most promising. Methodologically, it is demonstrated how simple concepts of partial order theory can be applied.